Screening and Identification of a Novel Anti-tuberculosis Compound That Targets Deoxyuridine 5′-Triphosphate Nucleotidohydrolase - Zhang, Yu; Zhang, Hongjuan; Chen, Ying; Qiao, Luyao; Han, Yanxing; Lin, Yuan; Si, Shuyi; Jiang, Jian-Dong (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is still a threat to humans worldwide. The rise of drug-resistant TB strains has escalated the need for developing effective anti-TB agents. Deoxyuridine 5’-triphosphate nucleotidohydrolase (dUTPase) is essential for thymidylate biosynthesis to maintain the DNA integrity. In Mycobacterium tuberculosis, dUTPase provides the sole source for thymidylate biosynthesis, which also has the specific five-residue-loop and the binding pockets absent in human dUTPase. Therefore, dUTPase has been regarded as a promising anti-TB drug target. Herein, we used a luminescence-based dUTPase assay to search for the inhibitors target Mycobacterium tuberculosis dUTPase (Mt-dUTPase) and identified compound F0414 as a potent Mt-dUTPase inhibitor with an IC50 of 0.80 ± 0.09 μM. F0414 exhibited anti-TB activity with low cytotoxicity. Molecular docking model and site-directed mutation experiments revealed that P79 was the key residue in the interaction of Mt-dUTPase and F0414. Moreover, F0414 was shown to have stronger binding with Mt-dUTPase than with Mt-P79A-dUTPase by SPR detection. Interestingly, F0414 exhibited insensitivity and weak directly binding on human dUTPase compared with that on Mt-dUTPase. All the results highlight that F0414 is the first compound reported to have anti-TB activity by inhibiting Mt-dUTPase, which indicates the potential application in anti-TB therapy.